2018
DOI: 10.1371/journal.pone.0200018
|View full text |Cite
|
Sign up to set email alerts
|

Study of specific nanoenvironments containing α-helices in all-α and (α+β)+(α/β) proteins

Abstract: Protein secondary structure elements (PSSEs) such as α-helices, β-strands, and turns are the primary building blocks of the tertiary protein structure. Our primary interest here is to reveal the characteristics of the nanoenvironment formed by both PSSEs and their surrounding amino acid residues (AARs), which might contribute to the general understanding of how proteins fold. The characteristics of such nanoenvironments must be specific to each secondary structure element, and we have set our goal here to gath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…After removing the non-normally distributed data and the correlated descriptors, 14 tests were applied. Next we present each STING_RDB descriptor and between parentheses a number indicating in how many tests each of them was used: "hydrophobic_WNADist" (5), "hbmwwm_WNADist" (5), "hbmwws_WNADist" (4), "Dihedral_Chi(3)" (4), "hydropho-bic_WNASurf" (3), "hbmwws_WNASurf" (3), "hbmwwm_WNASurf" (3), "hbmwm_WNA-Dist" (3), "ch_repulsive_WNADist" (3), "Number_Unused_Contact" (2), "hbswws_WNADist" (2), "hbss (2), hbmwwm" (2), "hbmws_WNADist" (2), "hbmm" (2), "Electrostatic_Potential_at_LHA_WNADist" (2), "Electrostatic_Potential_at_LHA" (2), "ch_repulsive_WNASurf" (2), "ch_repulsive" (2), "ch_attractive" (2), "aromatic_WNASurf" (2), "Number_Unused_Contact_WNASurf" (1), "hbswws" (1), "hbsws_WNADist" (1), "hbsws" (1), "hbss_WNASurf" (1), "hbmwws" (1), "hbmws_WNASurf" (1), "hbmwm_WNA-Surf" (1), "hbms_WNASurf" (1), "hbmm_WNADist" (1), "Electrostatic_Potential_Avera-ge_WNASurf" (1), "Electrostatic_Potential_Average_WNADist" (1), "Electrostatic_Potential_at_LHA_WNASurf" (1), "disulfide_WNASurf" (1), "Dihedral_Chi (4)" (1), "Dihedral_Chi(2)" (1), "Dihedral_Chi(1)" (1), "Cross_Pres_Order_CA" (1), "Cross_-Link_Order_CA" (1), "aromatic_WNADist" (1) For the all-β proteins, subtype: one strand only dataset, we have 12 lengths: 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 and 16. After removing the non-normally distributed data and the correlated descriptors, 3 tests were applied.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…After removing the non-normally distributed data and the correlated descriptors, 14 tests were applied. Next we present each STING_RDB descriptor and between parentheses a number indicating in how many tests each of them was used: "hydrophobic_WNADist" (5), "hbmwwm_WNADist" (5), "hbmwws_WNADist" (4), "Dihedral_Chi(3)" (4), "hydropho-bic_WNASurf" (3), "hbmwws_WNASurf" (3), "hbmwwm_WNASurf" (3), "hbmwm_WNA-Dist" (3), "ch_repulsive_WNADist" (3), "Number_Unused_Contact" (2), "hbswws_WNADist" (2), "hbss (2), hbmwwm" (2), "hbmws_WNADist" (2), "hbmm" (2), "Electrostatic_Potential_at_LHA_WNADist" (2), "Electrostatic_Potential_at_LHA" (2), "ch_repulsive_WNASurf" (2), "ch_repulsive" (2), "ch_attractive" (2), "aromatic_WNASurf" (2), "Number_Unused_Contact_WNASurf" (1), "hbswws" (1), "hbsws_WNADist" (1), "hbsws" (1), "hbss_WNASurf" (1), "hbmwws" (1), "hbmws_WNASurf" (1), "hbmwm_WNA-Surf" (1), "hbms_WNASurf" (1), "hbmm_WNADist" (1), "Electrostatic_Potential_Avera-ge_WNASurf" (1), "Electrostatic_Potential_Average_WNADist" (1), "Electrostatic_Potential_at_LHA_WNASurf" (1), "disulfide_WNASurf" (1), "Dihedral_Chi (4)" (1), "Dihedral_Chi(2)" (1), "Dihedral_Chi(1)" (1), "Cross_Pres_Order_CA" (1), "Cross_-Link_Order_CA" (1), "aromatic_WNADist" (1) For the all-β proteins, subtype: one strand only dataset, we have 12 lengths: 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 and 16. After removing the non-normally distributed data and the correlated descriptors, 3 tests were applied.…”
Section: Plos Onementioning
confidence: 99%
“…Previous work indicated that the Kolmogorov-Smirnov test is partially useful but certainly not the best way to analyze the nanoenvironment of a secondary structure element [ 1 ]. As demonstrated in Table 3 , at best, we found 54.79% of analyzed cases with a p-value < 1e-6.…”
Section: Manovamentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 lists those descriptors for which the Kolmogorov-Smirnov (KS) test yielded a p-value lower than 1e − 6 in more than 80% of the cases of the secondary structures. We applied tests for sets of proteins classi ed as either all-α or as α-helices in (α + β) + (α/β) (19).…”
Section: Introductionmentioning
confidence: 99%
“…As indicated, this paper is the third in a series about the nano environments of secondary structure elements. Two previous papers separately considered α-helices (19) and β-sheets (20).…”
Section: Introductionmentioning
confidence: 99%